2014
DOI: 10.1136/annrheumdis-2013-204832
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of osteoporotic fractures in patients with systemic sclerosis: a nationwide population-based study

Abstract: SSc patients had a high IR of vertebral and hip fractures, especially those who were female, older, used a high dose of corticosteroid or experienced bowel dysmotility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 25 publications
2
21
0
6
Order By: Relevance
“…Thus, all results could be applicable to this category of patients. The main limitation of our study is the small size of our population ( n = 33) as compared to a nationwide population-based study [ 33 ]. However, SSc is a rare disease and the number of included patients in our study is relative, compared to the number of previous studies concerned with bone damage in SSc.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, all results could be applicable to this category of patients. The main limitation of our study is the small size of our population ( n = 33) as compared to a nationwide population-based study [ 33 ]. However, SSc is a rare disease and the number of included patients in our study is relative, compared to the number of previous studies concerned with bone damage in SSc.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, GC did not appear in any of our models as an explanatory factor. There is a scientific debate about the impact of GC on BMD and OP in SSc: it has been showed that GC did not influence the occurrence of OP in SSc [ 34 ] and that cumulative GC doses did not differ between women with or without osteoporosis fractures, which is in contrast with the role of GC in the occurrence of fractures reported by Lai et al [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…[13] при обследовании 61 женщины с ССД в возрасте 26-51 года и 60 больных в постменопаузе не наблюдали ассоциации снижения МПКТ с предыдущим приемом ГКС во всех возрастных группах больных. Вместе с тем в большом популяционном исследовании, проведенном в Тайване и включавшем 1712 больных ССД (79% женщин), многофакторный регрессионный анализ показал тесную связь приема ГКС в суточной дозе >7,5 мг с развитием ОП и остеопоротических переломов у больных ССД [29].…”
Section: Discussionunclassified
“…The Ministry also established the NHI database which has collected the dates of birth, the diagnoses of patients, the dates of doctor’s visits, sex, and other related information of patients. Numerous studies utilize this database to survey the risk of comorbidities in diseases including systemic sclerosis and Crohn’s disease [ 7 , 8 ].…”
Section: Methodsmentioning
confidence: 99%